N-Palmitoylethanolamine Administration Ameliorates the Clinical Manifestation and Progression of Experimental Autoimmune Encephalomyelitis in Rodents - D. Impellizzeri; R. Di Paola; A. Ahmad; R. Crupi; I. Paterniti; M. Campolo; G. Bruschetta; S. Clemente; E. Esposito; S. Cuzzocrea (European Journal of Inflammation, 2014)
Experimental autoimmune encephalomyelitis in rodents (EAE) is an accepted in vivo model for immunopathogenic mechanisms underlying multiple sclerosis (MS) and tests possible treatment options because it mimics many of the disease patterns. The current treatments for delaying MS progression include cytostatic, immunomodulatory drugs such as mitoxantrone, cyclophosphamide (CY), biological agents such as interferon (IFN)-beta, natalizumab and random polymer glatiramer acetate. Unfortunately, all of these compounds have potentially serious side effects, some require systemic administration, and the biological agents are costly and immunogenic, causing response failure during prolonged treatment. With this aim in mind, the purpose of the current research was to examine the effects of endogenous substances such as N-palmitoylethanolamine (PEA). PEA is an endogenous fatty acid amide belonging to the family of the N -acylethanolamines (NAEs). Recently, several studies demonstrated that PEA is an important analgesic, anti-inflammatory and neuroprotective mediator, acting at several molecular targets in both central and sensory nervous systems as well as immune cells. The effect of PEA daily administered was investigated in rats and mice developing EAE. A multidisciplinary approach was employed to study behavior and biochemical parameters. In our study we found that PEA counteracts the clinical course and pathology of monophasic EAE in myelin basic protein-immunized Lewis rats and the progression of EAE induced in C57BI/6 mice by immunization with myelin oligodendrocyte glycoprotein. Our results show that PEA treatment had a beneficial effect on the two different EAE models.